Alice's adventures in Wonderland [compact disc, unabridged] ; &, Through the looking-glass - Carroll, Lewis, 1832-1898 (Blackstone Audio, 2008)
Alice's adventures in Wonderland begins with Alice chasing the White Rabbit down a rabbit hole, where she meets characters like the Mad Hatter and the Queen of Hearts. The sequel, Through the looking-glass, finds Alice in a fantastic land where everything is reversed.